(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Learning a foreign language is a complex process that involves not only cognitive abilities but also various psychological factors. Many learners encounter psychological barriers that hinder their progress and reduce their motivation. These barriers include language anxiety, fear of making mistakes, low self-confidence, lack of motivation, and negative past learning experiences. Such factors can significantly affect learners’ performance, participation, and overall success in language acquisition. This thesis examines the main psychological obstacles faced by foreign language learners and analyzes their impact on the learning process